2022
DOI: 10.1007/s40487-022-00208-1
|View full text |Cite
|
Sign up to set email alerts
|

Lanreotide Depot to Treat Gastroenteropancreatic Neuroendocrine Tumors in a US Community Oncology Setting: A Prospective, Observational Study

Abstract: Introduction Gastroenteropancreatic neuroendocrine tumors (GEP-NETs) can result in symptoms such as diarrhea, flushing, abdominal pain, and fatigue and are often associated with a significant disease burden and poor prognosis. This non-interventional, prospective, observational study evaluated the real-world safety and effectiveness of lanreotide depot, a somatostatin analog (SSA) used to treat GEP-NETs, in a community setting. Methods In this prospective, non-intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Long-lasting octreotide is registered in midgut NEN and functional NEN of the stomach, intestines, and pancreas. These distinctive differences and the fact that the application of lanreotide in autogel is more accessible and can be performed by the patient themselves or by an educated family member; these are the advantages of this treatment [60][61][62][63]. Ryan et al's study compared octreotide and lanreotide, finding no differences in their biochemical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting octreotide is registered in midgut NEN and functional NEN of the stomach, intestines, and pancreas. These distinctive differences and the fact that the application of lanreotide in autogel is more accessible and can be performed by the patient themselves or by an educated family member; these are the advantages of this treatment [60][61][62][63]. Ryan et al's study compared octreotide and lanreotide, finding no differences in their biochemical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Some 60% of NETs have either a pancreatic or gastrointestinal primary source (i.e., appendix, colon, intestine, rectum, stomach), collectively termed gastroenteropancreatic NETs [6]. Approximately 30% of NETs are functionally secretory, producing bioactive peptides and neuroamines which can cause fatigue, abdominal discomfort, muscle weakness, or dermal flushing/cutaneous vasodilation [7]. Among all NETs, those of duodenal origin comprise only 1-3% with clinical manifestations similar to other digestive tract tumors, resulting in nonspecific and variable clinical symptoms [8].…”
Section: Discussionmentioning
confidence: 99%
“…The median progression-free survival rate was similar, being 12 months (octreotide LAR) and 10.8 months (lanreotide depot) [33]. Another prospective, real-world setting study on adults with locally inoperable, metastatic GEP NENs using lanreotide depot identified a 2-year progression-free survival rate of 73% and a 2-year overall survival rate of 84%, while the rate of therapy-related adverse events was observed for 19.2% of patients, with a rate of 0% being observed for serious adverse effects [34].…”
Section: The Use Of Somatostatin Analogues (Ssas)mentioning
confidence: 99%